Repositioning of Lansoprazole as a Protective Agent Against Cisplatin-Induced Ototoxicity - Wakai, Eri; Ikemura, Kenji; Mizuno, Toshiro; Takeuchi, Kazuhiko; Tamaru, Satoshi; Okuda, Masahiro; Nishimura, Yuhei (Frontiers in Pharmacology, 2022)
Cisplatin (CDDP) is a well-known chemotherapeutic drug approved for various cancers. However, CDDP accumulates in the inner ear cochlea via organic cation transporter 2 (OCT2) and causes ototoxicity, which is a major clinical limitation. Since lansoprazole (LPZ), a proton pump inhibitor, is known to inhibit OCT2-mediated transport of CDDP, we hypothesized that LPZ might ameliorate CDDP-induced ototoxicity (CIO). To test this hypothesis, we utilized in vivo fluorescence imaging of zebrafish sensory hair cells. The fluorescence signals in hair cells in zebrafish treated with CDDP dose-dependently decreased. Co-treatment with LPZ significantly suppressed the decrease of fluorescence signals in zebrafish treated with CDDP. Knockout of a zebrafish homolog of OCT2 also ameliorated the reduction of fluorescence signals in hair cells in zebrafish treated with CDDP. These in vivo studies suggest that CDDP damages the hair cells of zebrafish through oct2-mediated accumulation and that LPZ protects against CIO, possibly inhibiting the entry of CDDP into the hair cells via oct2. We also evaluated the otoprotective effect of LPZ using a public database containing adverse event reports. The analysis revealed that the incidence rate of CIO was significantly decreased in patients treated with LPZ. We then retrospectively analyzed the medical records of Mie University Hospital to examine the otoprotective effect of LPZ. The incidence rate of ototoxicity was significantly lower in patients co-treated with LPZ compared to those without LPZ. These retrospective findings suggest that LPZ is also protective against CIO in humans. Taken together, co-treatment with LPZ may reduce the risk of CIO.